The Role of Anti-Bullying Ambassadors in Reducing Bullying in Elementary Schools - Dafit, Febrina; Yolanda, Feby (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This paper presents the role of anti-bullying ambassadors in reducing bullying cases at SD Negeri 193 Pekanbaru. The research background is the high incidence of bullying in elementary schools—physically, verbally, and socially—which negatively impacts students' emotional and social well-being. As a preventive measure, the school implemented an anti-bullying ambassador program that involves students as agents of change to create a safe and supportive school environment. This research uses a qualitative approach with a case study method. Data collection techniques include interviews, observations, and documentation. The informants consist of mentor teachers, ambassador students, and students who have been victims of bullying. The results show that anti-bullying ambassadors perform three main roles: as peer counsellors, companions to victims, and motivators who encourage students to speak up and reject bullying. This program has proven effective in reducing bullying and fostering a culture of mutual respect within the school.